Strategi Guru PAI Sebagai Intelektual Organik dalam Penguatan Keteladanan dan Kesadaran Sosial Peserta Didik: Studi Integratif Pemikiran Antonio Gramsci dan Albert Bandura - Yusron Nur Hadi; Agus Sutiyono; Agus Mutohar; Muhammad Ihsan; Nurul Laely Mahmudah; Fauzul Muna (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The increasing incidence of violence, bullying, and the degradation of social values in school environments signals a crisis of role modeling within educational practice. This article aims to analyze and formulate strategies for Islamic Religious Education (IRE) teachers in fostering students’ role modeling and social awareness through the integration of Albert Bandura’s social cognitive learning theory and Antonio Gramsci’s concept of organic intellectuals. This study employs a qualitative approach using a library research method, drawing on primary and secondary literature relevant to issues of role modeling, social awareness, and Islamic religious education. Data were analyzed descriptively and analytically through content analysis and hermeneutic interpretation to construct a coherent theoretical synthesis. The findings indicate that IRE teachers, as organic intellectuals, play a strategic role as moral exemplars and agents of social consciousness formation through reflective role modeling, contextual learning, and active engagement in social activities. The integration of Bandura’s and Gramsci’s theories emphasizes that value internalization occurs not merely through knowledge transmission, but through observation, lived experience, and continuous critical reflection. Consequently, strengthening the role of IRE teachers as moral exemplars and drivers of social values has the potential to create a more humanistic, empathetic, and civilized educational ecosystem.